Modeling change in memory performance and memory perceptions: findings from the ACTIVE study - Parisi, Jeanine M; Gross, Alden L; Rebok, George W; Saczynski, Jane S; Crowe, Michael; Cook, Sarah E; Langbaum, Jessica B S; Sartori, Andrea; Unverzagt, Fredrick W (Psychology and aging, 2011)
Within the context of the ACTIVE study, the current investigation explored the relationships between objective memory and two components of subjective memory (frequency of forgetting and use of external aids) over a five-year period. Relationships were assessed using parallel process latent growth curve models. Results indicated that changes in objective memory were associated with changes in perceived frequency of forgetting, but not with use of external aids (calendars, reminder notes) over time. Findings suggest that memory complaints may accurately reflect decline in objective memory performance, but that these memory changes are not necessarily related to compensatory behaviors.